Katharina von Bora: Geschichtliches Lebensbild - Thoma, Albrecht, 1844-1915 (Salt Lake City, UT : Project Gutenberg, 2004)
"Katharina von Bora: Geschichtliches Lebensbild" by Albrecht Thoma is a historical account written in the late 19th century. The text delves into the life of Katharina von Bora, the wife of Martin Luther, exploring her background, early life in a convent, and her significant role in the reformative era alongside her husband. The book aims to shine a light on a woman whose contributions have often been overshadowed by her husband's prominence. The opening of the narrative introduces Katharina von Bora's family history and the socio-political context of 16th-century Saxony, incorporating details about her early life and upbringing. It emphasizes the humble beginnings of her family and her entry into the convent at a young age, which was common for girls of her social status during that era. Thoma outlines the daily life in the convent, highlighting the strict religious rules and the challenges faced, foreshadowing her later actions, including her flight from the convent and eventual marriage to Luther. The beginning positions Katharina not only as a supportive partner but as a character of intrinsic complexity shaped by her experiences and the historical landscape surrounding her. (This is an automatically generated summary.)
Release date is 2004-06-01
Produced by Charles Franks and the DP Team
Keywords: Luther, Katharina von Bora, 1499-1552; Luther, Martin, 1483-1546; Reformation -- Germany -- Biography